2017
DOI: 10.21147/j.issn.1000-9604.2017.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Is new American Thyroid Association risk classification for hereditary medullary thyroid carcinoma applicable to Chinese patients? A single-center study

Abstract: ObjectiveThe American Thyroid Association (ATA) proposed a new risk classification for hereditary medullary thyroid carcinoma (MTC) in 2015. This study aimed to assess whether the new guidelines are suitable for the Chinese population, and reported our experience on prophylactic thyroidectomy.MethodsA total of 73 patients from 22 families were screened as rearranged during transfection (RET) mutation carriers from 2010 to 2016 in Cancer Hospital, Chinese Academy of Medical Science; the medical history for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…pathogenic variants from countries across five continents (excluding Brazil, Denmark, France, Germany, Italy, Japan, Norway, UK, and USA). Tyr606Cys, p.Cys618Tyr, p.Cys618Arg, p.Cys618Ser, p.Cys620Tyr, p.Leu790Phe, and p.Ser891Ala(97,98,99,100,101,102). Recently, there have been reports indicating the double pathogenic variants in the same patient, as in a large pedigree of 33 patients harboring p.Cys634/p.Asp707Glu, with a probably modifying effect in the age of onset and disease severity(103).…”
mentioning
confidence: 99%
“…pathogenic variants from countries across five continents (excluding Brazil, Denmark, France, Germany, Italy, Japan, Norway, UK, and USA). Tyr606Cys, p.Cys618Tyr, p.Cys618Arg, p.Cys618Ser, p.Cys620Tyr, p.Leu790Phe, and p.Ser891Ala(97,98,99,100,101,102). Recently, there have been reports indicating the double pathogenic variants in the same patient, as in a large pedigree of 33 patients harboring p.Cys634/p.Asp707Glu, with a probably modifying effect in the age of onset and disease severity(103).…”
mentioning
confidence: 99%
“…In this first comprehensive report on hMTC patients from India studying the genotype and phenotype, we found that the overall survival rates did not differ between the three ATA risk‐groups. This is in stark variance to the conventional notion that the RET genotype in hMTC correlates with the disease aggressiveness and outcomes [27, 28]. It seems prudent that the current ATA genotype based risk grouping system is relevant to those detected by the genetic screening.…”
Section: Discussionmentioning
confidence: 95%
“…Traditional concepts believe that the RET genotype of HMTC is closely related to the invasiveness of the disease. Further studies show that the high-risk group was significantly more aggressive than the medium-risk group, and patients with high-risk mutations had a significantly later clinical stage at initial diagnosis [32].…”
Section: The Risk Level Of Ret Mutations Involved In Fmtcmentioning
confidence: 93%